2018
DOI: 10.1055/s-0038-1670661
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Treatment Satisfaction with Dabigatran versus Warfarin in Patients with Non-Valvular Atrial Fibrillation in China

Abstract: Background Anti-coagulant therapy satisfaction for patients with atrial fibrillation is a critical issue, which impacts on their treatment adherence and clinical outcomes. The disadvantages of long-term warfarin treatment are well-described, and novel oral anti-coagulants have become an alternative option. Materials and Methods We compared patient-reported treatment satisfaction with dabigatran versus warfarin in non-valvular atrial fibrillation (NVAF) patients in China. Treatment satisfaction was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Compared with warfarin, NOACs are more convenient to use, including advantages such as fixed dose regimens, no requirement for frequent blood monitoring, no food and drug restrictions and less risk of bleeding 26 27. In the current study, we found that there was a substantially increased use of NOACs in Chinese patients during the past few years.…”
Section: Discussionmentioning
confidence: 53%
“…Compared with warfarin, NOACs are more convenient to use, including advantages such as fixed dose regimens, no requirement for frequent blood monitoring, no food and drug restrictions and less risk of bleeding 26 27. In the current study, we found that there was a substantially increased use of NOACs in Chinese patients during the past few years.…”
Section: Discussionmentioning
confidence: 53%
“…The use of a therapy associated with higher satisfaction is a critical issue, due to its relationship to treatment adherence, 55,56 associated better anticoagulation control, 46 and consequently improved health outcomes. 49,57 Moreover, optimal adherence is essential to ensure both efficacy and safety with anticoagulant therapy and adherence to OACs remains a challenge in clinical practice. 3,5,13 A recent study that assessed 12-month adherence and persistence with OACs reported adherence rates of 63.1 to 66.5% with NOACs, compared with 55.2% with VKAs, and persistence with NOACs of 61.4 to 78.7%, compared with 65.9% with VKAs.…”
Section: Discussionmentioning
confidence: 99%
“…14,33,[44][45][46][47] Additionally, in some studies the outcome was assessed by nonblinded interviewers. 40,41,43,48,49 Moreover, in three studies there may be bias regarding the patients lost to follow-up. 33,42,44 Almost all of the trials included patients who had been on the same oral anticoagulant for at least 3 months, with two exceptions.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…These concerns from previous studies were raised by our patients. Although NOACs spared the need for INR monitoring, the cost of NOACs could be a factor that deters patients from using it (40). In our study, none of our patients prioritized cost over the e cacy and bene ts that NOACs brought.…”
Section: Discussionmentioning
confidence: 67%